Technical aspects of video-assisted and robotic-assisted thoracoscopic segmentectomy - Lutz, Jon A.; Kocher, Gregor J. (Journal of Thoracic Disease, 2017)
Li and co-authors very nicely presented their technique of robot-assisted thoracic surgery (RATS) S6-segmentectomy illustrated by high quality figures (1). They presumably base their approach on the excellent book of Nomori and Okada (2), one of the most important references for open segmentectomy of the lung.